2018
DOI: 10.30604/jika.v3i2.93
|View full text |Cite
|
Sign up to set email alerts
|

Peran Bidan dalam ASI Eksklusif di Kabupaten Cilacap

Abstract: Exclusive breastfeeding led to decreasing 40 percent of children under-five mortality in Indonesia. Exclusive breastfeeding rate found in Cilacap in 2014 around 36,16 percent. Midwife role was able to increase exclusive breastfeeding. This research aim was to analyze midwife role on exclusive breastfeeding in Cilacap. Type of this study was a correlation descriptive with cross-sectional approach. Of 220 mothers who had babies aged 6-12 month in Puskesmas Cilacap Selatan I in 2014 collected by a cluster random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
3
0
2
Order By: Relevance
“…The findings of this study are similarly consistent with the findings of Majestika Septikasari's research (2017), which found a statistically significant relationship between midwife assistance and increased exclusive breastfeeding. The greater the level of assistance provided by the midwife, the greater the likelihood of success with exclusive breastfeeding (Majestika Septikasari, 2017). The findings of a study conducted by Norhayati Maslani (2015), which found that the midwife program had a substantial impact on exclusive breastfeeding, are comparable.…”
Section: Multivariate Analysismentioning
confidence: 99%
“…The findings of this study are similarly consistent with the findings of Majestika Septikasari's research (2017), which found a statistically significant relationship between midwife assistance and increased exclusive breastfeeding. The greater the level of assistance provided by the midwife, the greater the likelihood of success with exclusive breastfeeding (Majestika Septikasari, 2017). The findings of a study conducted by Norhayati Maslani (2015), which found that the midwife program had a substantial impact on exclusive breastfeeding, are comparable.…”
Section: Multivariate Analysismentioning
confidence: 99%
“…Menurut Maryunani (2015) untuk menunjang keberhasilan menyusui dalam manajemen laktasi, maka dalam pelaksanaannya terutama dimulai pada masa kehamilan, segera setelah persalinan, dan pada masa menyusui selanjutnya. Adapun upaya-upaya yang dapat dilakukan petugas kesehatan agar tercapai keberhasilan menyusui pada klien/pasiennya antara lain pada masa antenatal, intranatal, dan masa post-natal (masa menyusui) (Septikasari, M. 2018).…”
Section: Hubungan Peran Petugas Kesehatan Dengan Pemberian Asi Eksklusifunclassified
“…Berdasarkan seluruh jawaban responden mengenai peran bidan sebagai motivasi dalam promosi kesehatan pada ibu hamil dapat dilihat bahwa hampir seluruh responden setuju dengan adanya promosi kesehatan yang dilakukan oleh bidan, dengan adanya motivasi yang diberikan bidan maka cenderung akan meningkatkan informasi ibu hamil tentang masa kehamilan (Septikasari, 2018) serupa penelitian oleh (Tombokan et al, 2016), yang menunjukan hasil bahwa sesudah mendapatkan motivasi dan promosi kesehatan, pengetahuan ibu hamil dapat meningkat sehingga ibu hamil mengetahui tentang tanda bahaya kehamilan. Penelitian oleh (Sumardino & Sunarto, 2016) yang menunjukan bahwa sesudah mendapatkan motivasi dan promosi kesehatan, pengetahuan ibu hamil dapat meningkat sehingga ibu hamil dapat mengetahui tentang antenatal care dengan baik, penelitian oleh (Hutagaol, 2018) yang menunjukan hasil bahwa sesudah mendapatkan motivasi dan promosi kesehatan, pengetahuan ibu hamil tentang kesiapan birth preparedness terhadap kesiapan ibu hamil trimester III dapat meningkat.…”
Section: Pembahasanunclassified